Metamorfoses do cinema punk (1975-1990) - Araújo, Raphael Genuíno de (2016)
This research aims to analyze a number of film productions coming from the American punk and English environment, between the years 1976 - 1990, from reflections on their political, economic, and aesthetic appearance of corporeality punk. Search, first, u